ASPEK TUTUR DALAM GEGURITAN DHARMA SUNYATA - Astawa, I Wayan Buda (Humanis, 2013)
Geguritan Dharma Sunyata contains the basic teachings of Hinduism truth as a spiritual moral reflection, and guidance for mankind to freedom highs. This study aims to describe the structure of narrative and speech aspects as the contents of geguritan Dharma Sunyata. Methods and techniques used are divided into three stages, namely (1) phase refer to the provision of data using observe methods, supported by technical translation and recording techniques, (2) the stage of data analysis using qualitative methods supported by descriptive and analytical techniques, and (3) the presentation of the results of the data analysis stage using informal methods, supported by deductive and inductive techniques. The results of this research is to build a structure unfolding geguritan Dharma Sunyata. The narrative structure Include, background, character and characterization, theme and mandate, and aspects contained is, about ongkara, tatwamasi, karmaphala, sapta loka and deliverance.
Keywords: tutur, geguritan, structure